Identifying Croatian museums' indigenous visitors in a post-war era: perceptual examinations of one's own heritage. Issue 3 (27th May 2017) - Domic, Dino; Boukas, Nikolaos
Abstract : The paper focuses on the consumption of the past by indigenous people through the museum or heritage site within post-war Croatia. Through the application of an inductive, qualitative methodology, 'Critical Ethnography', an integrated theory of individual identity formation, which is both social and psychological in nature, is presented. The paper, which is the culmination of theory building, has been guided by in-depth interviews, observation of behaviour and the incorporation of theoretically sensitising literature. As a result of reflexive integration of both the data and the literature, three categories, which constitute the developed theory are derived and analysed in relation to the different ways of constructing meaning and experiences within the museum/heritage context. The labels assigned to each of the developed categories, the 'Fragmented self', the 'Paraphrenic self' and the 'Enlightened self' are a reflection of a part of the self, which identifies to varying extents with the ascribed post-war identity of 'Croat'. Furthermore, the three explanatory categories of behaviour look into the various ways with which the individual subject reflects upon and interprets his/her own past in relation to the formation of an acceptable post-war conception of his/her individual identity. The paper concludes that in order for a nation to project its cultural heritage worldwide through its museums and cultural sites, it needs first to understand and incorporate the indigenous' views of their own heritage and then to develop and communicate cultural heritage products through other industries, such as tourism.